2018
DOI: 10.1007/s40092-018-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of wire-cut EDM process parameter by Grey-based response surface methodology

Abstract: Wire electric discharge machining (WEDM) is one of the advanced machining processes. Response surface methodology coupled with Grey relation analysis method has been proposed and used to optimise the machining parameters of WEDM. A face centred cubic design is used for conducting experiments on high speed steel (HSS) M2 grade workpiece material. The regression model of significant factors such as pulse-on time, pulse-off time, peak current, and wire feed is considered for optimising the responses variables mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…As shown in Figure 7, a series of sampling points were generated through Latin Hypercube Sampling (LHS) of the DOE, and used to construct the response surface model between parameters and objective functions. Then, the optimal solution to the model was searched for by the multi-objective genetic algorithm (MOGA) of the GDO [15][16][17][18].…”
Section: Figure 7 the Optimal Design Routementioning
confidence: 99%
“…As shown in Figure 7, a series of sampling points were generated through Latin Hypercube Sampling (LHS) of the DOE, and used to construct the response surface model between parameters and objective functions. Then, the optimal solution to the model was searched for by the multi-objective genetic algorithm (MOGA) of the GDO [15][16][17][18].…”
Section: Figure 7 the Optimal Design Routementioning
confidence: 99%
“…The Grey model, abbreviated as GM, has been successfully applied in many disciplines (Hsu & Chen, 2003;Kumar et al, 2018;Ma & Wu, 2010;Truong & Ahn, 2012). Grey Model cannot be applied to many real situations and systems.…”
Section: Novel Grey Model (Gm) For Gas Lift Optimizationmentioning
confidence: 99%
“…The outcomes revealed that the WEDM responses were influenced by the POT, POFT, and CA, respectively. Additionally, the R a , one of the most important indicators of the surface integrity was optimized in conjunction with other factors, including the cutting speed (CS) [8], wire wear ratio (WWR) [9], kerf width (KW) [10][11][12], and material removal rate (MRR) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the effects of the varied conditions on machining responses for different WEDM operations have been performed. Different optimization techniques, such as the RSM [1,2,4,[6][7][8][9]13], Taguchi [3,14], grey relation analysis (GRA) [15], and hybrid approach [9,10,12] were utilized to resolve the optimizing issues. However, the published works regarding optimization in the WEDM performances have still the limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation